Effect of La₀.₆₇Aₒ.₃₃MnO₃ (A= Ba, Ca, Sr) manganites on the superconducting properties of YBa₂Cu₃O₇ˍδ - Baharuddin Pallan, Nur Fadilah (2013)
The discovery of YBa2Cu3O7-δ (YBCO) high temperature superconductors (HTS) has attracted worldwide researchers to study its ability to trap large magnetic flux. In this research, the effects on structural, phases, transport properties, and microstructural properties were investigated after addition of manganites in YBCO superconductor. Characterizations of samples were carried out by using x-ray diffraction (XRD), AC susceptometer (ACS), and scanning electron microscope (SEM). The samples that have prepared were pure YBCO and for the addition of manganites in YBCO superconductor, the manganites were La0.67Ca0.33MnO3 (LCMO), La0.67Ba0.33MnO3 (LBMO), and La0.67Sr0.33MnO3 (LSMO) with 0.2 wt%, 0.4 wt%, 0.6 wt%, 0.8 wt%, and 1.0 wt%. The polycrystalline samples of pure YBa2Cu3O7-δ and addition of manganites in YBCO were prepared by the solid state reaction method. The crystal structure for pure YBa2Cu3O7-δ is orthorhombic with space group Pmmm. XRD patterns showed the orthorhombic structure were retained for addition of LCMO at 0.2 wt% - 0.6 wt%. The structure changed to tetragonal after added with 0.8 wt% - 1.0 wt% of LCMO. The crystal structure was tetragonal after addition with 0.2 wt% - 1.0 wt% of LBMO. The crystal structure was tetragonal after addition with 0.2 wt% - 1.0 wt% of LSMO. AC Susceptometer measurement for manganite addition in YBCO revealed that the diamagnetic onset temperature, Tc-on decreases as the wt% of addition was increased. The temperature dependence ac susceptibility data for real part (χ’) showed Tc-on shifting towards lower temperature on all types of manganites addition as the weight percentage increased. The imaginary component, χ’’ showed decreases in the phase lock-in temperature (Tp) towards lower temperatures as the weight percentage of manganites increased. For pure YBCO, Tc-on is 90.2 K. The first part manganite addition is LCMO, highest Tc-on is 91.1 K for addition 0.2 wt%. The highest Tc-on is 91.0 K obtained from sample addition 0.8 wt% of LBMO. Addition 0.4 wt% of LSMO showed Tc-on 90.3 K as the highest Tc-on for the third part of manganites addition. Overall, the highest Tc-on obtained when used low ac field, 0.1 Oe for all types of manganites.. Addition of LCMO, LBMO, and LSMO in YBCO showed that the grains size decreases as the weight percentage of addition increased. The morphology of fractured surface and grains started to agglomerate for manganites in the range of 0.6 wt% until 1.0 wt%. When the amount addition of manganites increased, it’s changed the crystal structure because of oxygen deficiency and lattice parameter decreased. When the samples are not fully oxygen loaded it’s gave effect decreases of Tc-on. Role oxygen content in YBCO related with the dependence of Tc-on and lattice parameters of the YBCO compound. The decreases in Tc-on were due to poor connectivity among grains in the samples.